Acute cannabis intoxication among the paediatric population - Malta, Ginevra; Albano, Giuseppe Davide; Lavanco, Gianluca; Brancato, Anna; Cannizzaro, Carla; Argo, Antonina; Contorno, Simona; Plescia, Fulvio; Zerbo, Stefania (Frontiers in Toxicology, 2025)
This narrative review synthesizes the toxicological, clinical and medico-legal aspects of paediatric cannabis intoxication. By providing a comprehensive overview, it aims to inform future research, guide policymaking, and enhance clinical and toxicological practice in addressing this growing public health concern. The pharmacokinetics of cannabinoid ingestion in children are significantly influenced by the immaturity of their gastrointestinal tract and metabolic enzyme systems, resulting in altered oral bioavailability. Clinical data indicate that Δ9-tetrahydrocannabinol (THC)-related effects in paediatricpaediatric patients typically emerge within 2 hours of ingestion, with more severe symptoms developing within 4 hours. The endocannabinoid system (ECS) undergoes significant developmental changes, with marked differences in cannabinoid receptor expression and distribution across fetal, neonatal, and adult brains. During neurodevelopment, CB1 receptors exhibit unique expression patterns, including transient localization in brainstem regions critical for neurovegetative functions. These developmental dynamics likely explain children’s heightened sensitivity to THC’s neurological and neurovegetative effects, often resulting in more severe outcomes compared to adults. The reliable detection of cannabinoids involves integrating screening methods with confirmatory analytical techniques. Urine immunoassay testing is widely considered an helpful toolto assess a previous exposure, becoming positive within 3–4 h of ingestion. However, this method is prone to false positives. Plasma THC concentration, when measured close to the event, offers valuable insights into the quantity ingested and the correlation between exposure and clinical outcomes in the impairment window. Hair analysis, while useful for distinguishing between acute and chronic use, is susceptible to various biases. The rising incidence of acute cannabis intoxication in children underscores the urgent need for targeted public health interventions and stricter regulatory frameworks. Preventive measures such as child-resistant packaging, public education campaigns, and cannabis use screening during pregnancy are essential to mitigate risks. Clinicians should consider THC exposure in the differential diagnosis of children presenting with unexplained neurological, immune, or metabolic symptoms.